Family Caregivers’ Satisfaction towards the Communication of Health Service Providers in Tertiary Care Hospital of Nepal - Shrestha, Sonam; Maharjan, Basant; Acharya, Swosti; Dangol, Manisha; Shrestha, Sunil (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Patient and family caregivers’ satisfaction is an essential measure of the quality of care and a determinant of health service utilization. Measuring family caregivers’ satisfaction with health service providers is important for understanding and improving the quality of care at health facilities. Therefore, the present study aimed to assess the satisfaction of family caregivers towards the communication of health service providers.Methods: A descriptive cross-sectional study was conducted by the development of a questionnaire at one of the tertiary care hospitals. Self-administered questionnaires related to demography and different dimensions on the satisfaction of caregivers towards the communication of health service provider was designed. Sixty caregivers were provided questionnaire and data was collected. Descriptive analysis, frequency, and percentage were calculated using SPSS 23 (SPSS Inc., Chicago, IL, USA)Results: The study showed that the majority of the caregivers (40%) were of the young age group (31-40 years). More than half (53%) of the caregivers were satisfied with different ways of communication about the patient's condition and treatment. In terms of communication mode, the majority of the caregivers were satisfied with related different ways of communication about the patient's condition and treatment (53.3%) followed by verbal (63.6 %) and non-verbal (50.6 %) respectively during their stay at the hospital.Conclusion: The current study found that caregivers were satisfied with the communication provided by health service providers. This suggests that the treatment provided to patients might have better outcome measures. Additionally, it may help to reduce the anxiety among caregivers regarding the patients’ condition.